Formal Dining at Cambridge Colleges: Linking Ritual Performance and Institutional Maintenance - Dacin, M. Tina; Munir, Kamal; Tracey, Paul (Academy of Management Journal, 2010)
We examine the role of rituals in institutional maintenance. Through an in-depth, qualitative study of formal dining at the University of Cambridge, we explore how the performance of these rituals contributes to the maintenance of the British class system. We find that rituals are important for institutional maintenance because they have a powerful bearing on participants beyond the confines of the rituals themselves. Our analysis also suggests that institutions are refracted through context and individual experience at a micro level, and indicates a more fragmented and less strategic conception of institutional maintenance than is portrayed in recent work.